The museum as a space of social care - Morse, Nuala (Abingdon, Oxon Routledge, Taylor & Francis Group, 2021)
This book examines the practice of community engagement in museums through the notion of care. It focuses on building an understanding of the logic of care that underpins this practice, with a view to outlining new roles for museums within community health and social care. This book engages with the recent growing focus on community participation in museum activities, notably in the area of health and wellbeing. It explores this theme through an analysis of the practices of community engagement workers at Tyne & Wear Archives & Museums in the UK. It examines how this work is operationalised and valued in the museum, and the institutional barriers to this practice. It presents the practices of care that shape community-led exhibitions, and community engagement projects involving health and social care partners and their clients. Drawing on the ethics of care and geographies of care literatures, this text provides readers with novel perspectives for transforming the museum into a space of social care. This book will appeal to museum studies scholars and professionals, geographers, organisational studies scholars, as well as students interested in the social role of museums -- Provided by publisher.engagement as care work -- 6. Curatorial work and care -- 7. The museum as a space of social care.
1. Introduction -- PART I: The participatory turn in museums: 2. The problem of engagement PART II: The institutional life of community engagement workers: 3. The language of community engagement -- 4. Managing community engagement PART III: The emotional life of community engagement workers: 5. engagement as care work -- 6. Curatorial work and care -- PART IV: Social care in the museum: 7. The museum as a space of social care -- 3. The power of objects: little things please little minds? / Nicola Wallis -- 4. The thing-ness of wood chips / Lisa Howarth -- 5. Bright and Shiny: infants, toddlers and contemporary art at the Ipswich Art Gallery / Barbara Piscitelli
Includes bibliographical references and index.
Keywords: Museums -- Social aspects